The Right to Land: To Whom Belongs after a Reconciliation Law in Egypt - Ahmed Mounir Soliman (Alanya Hamdullah Emin Paşa Üniversitesi, 2022)
A revolutionary book by De Soto to formalize land tenure by changing “dead capital” to “life capital” has become the trademark in Egypt of issuing a temporary reconciliation law of 2019 and its amendment to approve a legal certificate to the violators against a certain fee. The question is does this law legalize informal housing? Is it enough to introduce a legal certificate to secure land tenure for the violators? How would this law apply on the ground? Depending on the deductive methodology, this paper traces sociotechnical transitions concerning legalizing the status quo of building/land, tenure security, real-estate markets (formal/informal) caused by laws on buildings violations reconciliation. The idea is to take a step back and look at a wide-angle of the problem in the future to arrive at a clear picture of the influences of the introduction of a new law on the land market, before making a decision. The paper assumes that the temporary reconciliation law in Egypt is opening the debate on the alteration of land management to govern the status quo of the chaos of the right to land. It concludes this temporary reconciliation law has created a state of decayed/wealth, social inclusion/exclusion of the bottom of the social pyramid nevertheless to whom the justification is affected.